Comparative Analysis Of Financial Performance Before And After The Implementation Of International Financial Reporting Standard (IFRS) (Empirical Study on Mining Sector Companies Listed on the Indonesia Stock Exchange) - Riani, Nita; Yuliusman, Yuliusman; Friyani, Rita (Faculty of Economics and Business Universitas Jambi, 2023)
This study aims to examine differences in financial performance before and after the adoption of International Financial Reporting Standards (IFRS) in mining companies listed on the Indonesia Stock Exchange. Financial performance is assessed using profitability (ROA, ROE), solvency (DAR, DER), and liquidity (CR, QR) ratios. A comparative quantitative approach was employed, analyzing company data from periods prior to and following IFRS implementation. The results show that IFRS adoption led to noticeable differences in return on assets and current ratio, indicating a shift in asset utilization efficiency and liquidity management. However, return on equity, debt ratios, and quick ratio did not show significant changes, suggesting that IFRS implementation had limited influence on capital structure and short-term liquidity measures in the mining sector. These findings imply that IFRS adoption may selectively impact certain financial aspects, particularly those related to internal efficiency and operational cash flow. For corporate managers, aligning financial strategies with IFRS standards can enhance decision-making and performance evaluation. Regulators may also benefit from understanding the sector-specific effects of IFRS to ensure relevant and effective policy implementation. Investors are encouraged to consider both the opportunities and limitations of IFRS-based reports in their financial analysis.